The Marginalization of Sustainable Charcoal Production in the Policies of a Modernizing African Nation - Doggart, Nike; Meshack, Charles (Frontiers in Environmental Science, 2017)
Charcoal is the main cooking fuel for urban populations in many African countries. Urbanisation and population growth are driving an increase in demand for charcoal, whilst deforestation reduces biomass stocks. Given increasing demand for charcoal, and decreasing availability of biomass, policies are urgently needed that ensure secure energy supplies for urban households and reduce deforestation. There is potential for charcoal to be produced sustainably in natural woodlands, but this requires supportive policies. Previous research has identified policy issues that have contributed to the charcoal sector remaining informal and environmentally destructive. In this paper, we describe how national policies in Tanzania on energy, forests, agriculture, land, and water, consider charcoal, and the degree to which they do, and do not, support sustainable charcoal production. The paper identifies policy gaps and a cross-sector tendency to marginalise natural forest management. By adopting a nexus approach, the paper highlights the inter-connections between sustainable charcoal production, ecosystem services, and trade-offs in the allocation of land, labour, and net primary production. In conclusion, sustainable charcoal production has been marginalised in multiple national policies. As a result, potential benefits of sustainable charcoal production are lost to multiple sectors.